Teoria stylu i jej fundamenty - Gajda, S. (Мовознавство, 2017)
Автор статті пропонує цілісну й водночас незавершену теорію стилю, яка може стати основою стилістичних досліджені ґрунтується на моделі наукової теорії, в якій виділяються три рівні (філософський, теоретико-методологічний та емпіричний). На рівні мовної онтології автор виходить із припущення про чотири способі її існування (конкретні мовні дії та їхні текстуальні результати, мовна система, а також індивідуальна і колективна мовна свідомість) і, відповідно, вирізняє стиль конкретного тексту і системний, індивідуальний та колективний стилі. Розвиток концепції стилю в теоретико-методологічній площині вимагає врахування відношень між мовою-стилем-текстом і світом, людиною, соціумом, мисленням і культурою. Ці відношення впливають на висвітлення стильових явищ на емпіричному рівні, де багаті здобутки стилістики можуть інтегруватися завдяки цілісній теорії і холістичному, поряд з аналітико-редукціоністським, характерові сучасної науки. The author presents an outline of a complete, yet unfinished, theory of style. The outline can make the foundation of a stylistic research program. A full scientific theory possesses a structure within which one can distinguish three levels: 1) philosophical (ontological assumptions as well as epistemological-axiological ones); 2) theoretical-methodological (a set of highly abstract notions and theorems which conceptualize and structure the fragment of reality that is described and explained); 3) empirical (a set of notions and descriptive-observational theorems, stating something directly about the examined fragment). By making reference to philosophical ontology the author accepts — on the ground of linguistic ontology — an assumption of four ways, ones which are mutually connected and constitute a oneness: 1) concrete linguistic actions and their textual products; 2) language system; 3) individual consciousness of language, and 4) collective awareness of language. Beginning with the idea of style as a humanistic structure of text, one can respectively speak about the following: 1) the style of a concrete text; 2) the comprehensive style (precisely speaking about stylistic models in the common norm); 3) individual styles as components of the language consciousness of individuals; 4) collective styles as components of language awareness of given communities. Developing theories of style on the theoretical-methodological level requires considering the relation between language-text-style and the world, man, society, as well as mind and culture. These relations impinge on the vision of style-related phenomena considered on the empirical level. The rich accomplishments of stylistics can be united thanks to the integrative power of a complete theory and the increasingly stronger integrative-holistic trend in the development of science, which is complementary towards the analytical-reductive tendency.